URGENSI MATERI PEMBELAJARAN AKHLAK K.H. HASYIM ASY’ARI DALAM MENGHADAPI TANTANGAN PEMBELAJARAN ABAD 21 - Ahmad Dwi Nur Khalim (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2020)
21st century learning discourse is getting bigger in the current global world. All countries are competing to prepare the best possible human resources. It's just that if not accompanied by morals will backfire for the country. This study aims to look at the urgency of the moral learning material of ideas from K.H. Hasyim Asy’ari in welcoming 21st century learning. This research is library research. The data source is obtained from the book of adab al-‘alim wa al-muta’alim. Methods of data analysis using descriptive methods, the data obtained by documentation techniques. Then the descriptive data are analyzed deeper using content analysis. The results showed that in the book of adab al-‘alim wa al-muta’alim by K.H. Hasyim Asy’ari has education significance, ethics that students must possess (ethics in learning, ethics towards teachers, ethics towards subjects, ethics that must be possessed by teachers (teacher ethics, teacher ethics in teaching, teacher ethics to students, ethics towards books and learning media). While the urgency is clearly seen that the moral teaching material of K.H. Hasyim Asy'ari to directs close to Allah. hen with the moral teaching material K.H. Hasyim Asy’ari can equip characters in multiple dimension. And with these materials students can have a foundation of integrity in life.